2017
DOI: 10.1016/j.molp.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

DNA Topoisomerase 1 Prevents R-loop Accumulation to Modulate Auxin-Regulated Root Development in Rice

Abstract: R-loop structures (RNA:DNA hybrids) have important functions in many biological processes, including transcriptional regulation and genome instability among diverse organisms. DNA topoisomerase 1 (TOP1), an essential manipulator of DNA topology during RNA transcription and DNA replication processes, can prevent R-loop accumulation by removing the positive and negative DNA supercoiling that is made by RNA polymerases during transcription. TOP1 is required for plant development, but little is known about its fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 66 publications
1
25
0
Order By: Relevance
“…R-loops in plants have recently gained increasing attention. They have been found to play a role in regulating flowering time (Sun et al 2013), root development (Shafiq et al 2017), gene splicing (Conn et al 2017), and genome instability (Yang et al 2017). The first global characterization of R-loops in Arabidopsis thaliana revealed a potential role in gene activation by repressing the expression of antisense lncRNA (Xu et al 2017).…”
mentioning
confidence: 99%
“…R-loops in plants have recently gained increasing attention. They have been found to play a role in regulating flowering time (Sun et al 2013), root development (Shafiq et al 2017), gene splicing (Conn et al 2017), and genome instability (Yang et al 2017). The first global characterization of R-loops in Arabidopsis thaliana revealed a potential role in gene activation by repressing the expression of antisense lncRNA (Xu et al 2017).…”
mentioning
confidence: 99%
“…In plants, R-loops have been found to modulate the expression of the nuclear genes, thereby affecting plant development, such as flowering time regulation in Arabidopsis (Sun et al, 2013), and root development in rice (Shafiq et al, 2017). However, little is known about R-loop involvement in other biological processes in plants.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, R-loops were first reported to repress the expression of the antisense long noncoding RNA COOLAIR to promote flowering in Arabidopsis thaliana (Sun et al, 2013). Recently, we revealed that the maintenance of nuclear inherent R-loops in rice (Oryza sativa) auxin-related genes by OsTOP1 is essential for root development (Shafiq et al, 2017) and uncovered the distinct R-loop profile in the Arabidopsis nuclear genome (Xu et al, 2017). However, we still have a limited understanding of the mechanisms of R-loop formation and resolution or their biological functions in plants, especially in DNA-containing organelles such as chloroplasts and mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it is been reported that the regulation of R-loop levels could impact antisense transcription at FLC locus in Arabidopsis [24]. Moreover, the misexpression of topoisomerase 1, a key R-loop regulator, could compromise the expression of auxin-related genes in rice [25]. In addition, there are three RNase H1s with different organelle localization and the chloroplast-localized RNase H1 is critical for maintaining chloroplast genome integrity in Arabidopsis [26].…”
Section: Introductionmentioning
confidence: 99%